Self-consistency in the phonon space of the particle-phonon coupling model - Tselyaev, Victor; Lyutorovich, N.; Speth, J.; Reinhard, Paul-Gerhard (Physical Review C - Nuclear Physics, 2018)
In the paper the nonlinear generalization of the time blocking approximation (TBA) is presented. The TBA is one of the versions of the extended random-phase approximation (RPA) developed within the Green-function method and the particle-phonon coupling model. In the generalized version of the TBA the self-consistency principle is extended onto the phonon space of the model. The numerical examples show that this nonlinear version of the TBA leads to the convergence of results with respect to enlarging the phonon space of the model.
CRIS-Team Scopus Importer:2021-07-19